A contemporary evaluation of carotid endarterectomy outcomes in patients with chronic kidney disease in the United States. (October 2017) - Patel, Amit R; Dombrovskiy, Viktor Y; Vogel, Todd R
Objectives: Chronic kidney disease (CKD) has been identified as a significant risk factor for poor post-surgical outcomes. This study was designed to provide a contemporary analysis of carotid endarterectomy (CEA) outcomes in patients with CKD, end-stage renal disease (ESRD), and normal renal function (NF). Methods: The Nationwide Inpatient Sample data 2006–2012 was queried to select patients aging 40 years old and above who underwent CEA during two days after admission and had a diagnosis of ESRD on long-term hemodialysis, patients with non-dialysis-dependent CKD, or NF. Patients with acute renal failure were excluded. We subsequently compared procedure outcomes and hospital resource utilization in these patients. Results: Totally 573, 723 CEA procedures were estimated: 4801 (ESRD)‚ 32, 988 (CKD)‚ and 535, 934 (NF). Mean age was 71.0 years, 57.7% were males, and 73.7% were white. Overall hospital mortality was 0.20%: 0.69% (ESRD), 0.35% (CKD), and 0.19% (NF), p < 0.0005 between groups. The overall stroke rate was 1.6%: 1.8% (ESRD), 2.0% (CKD), and 1.6% (NF). Comparing NF to CKD there was a significant difference: p < 0.0001. For CKD patients, compared to NF patients, there was an increased risk in cardiac complications (odds ratio = 1.2; 95% CI 1.15–1.32), respiratory complications (odds ratio = 1.2; 95% CI 1.15–1.32), and stroke (odds ratio = 1.1; 95% CI 1.04–1.23). For ESRD patients compared to NF patients there was an increased risk in respiratory complications (odds ratio = 1.3; 95% CI 1.08–1.47) and sepsis (odds ratio = 4.4; 95% CI 3.23–5.94). Mean length of stay and cost were: 2.8 d and 13, 903 (ESRD), 2.2 d and 12, 057 (CKD), and 1.8 d and 10, 130 (NF), all p < 0.0001. Conclusions: Patients with ESRD undergoing CEA had an increased risk of respiratory and septic complications, but not a higher risk of stroke compared to patients with normal renal function. The greatest risks of postoperative stroke, respiratory, and cardiac complications were found in patients with CKD. A diagnosis of ESRD and CKD were both found to significantly increase hospital mortality, length of stay and cost. Where clinicians typically consider ESRD patients the highest risk for CEA, further consideration should be given to patients with CKD not yet on dialysis as they had the higher risk of cardiac complications and stroke compared to the others evaluated.